Turkey : Expanding Opportunities for the Next Generation - World Bank (Washington, DC, 2017)
This report is a part of larger welfare and social policy work agenda which the Turkish State Planning Organization and the World Bank are carrying out collaboratively. The work agenda includes the preparation of a number of conceptualized, and in part of co-authored, analytical studies on topics ranging from examines the equity determinants to investigating the links between poverty, employment creation, and growth. Further, the work agenda comprises a number of human development dialogues for which we are inviting international experts and practioners to share their experiences about social policy reforms with the Turkish government and the wider academic and non-governmental public. This report examines life chances. Life chances for today Turkish people, most importantly future generation, today's children. The results presented in this report show that life chances differ in important dimensions today, and that Turkey could immensely improve its human and economic development potential by maximizing such opportunities.